697Change of smoking habits by introducing and spreading heated tobacco products in Japan. (2nd September 2021) - Harada, Sei; Sata, Mizuki; Matsumoto, Minako; Takeuchi, Ayano; Iida, Miho; Kato, Suzuka; Hirata, Aya; Kuwabara, Kazuyo; Sugiyama, Daisuke; Okamura, Tomonori; Takebayashi, Toru
Abstract: Background: Heated tobacco product (HTP) users are rapidly increasing in Japan since 2014. Controlling HTPs is now one of the most urgent issues. We aimed to clarify the change of smoking habits by introducing and spreading HTPs. Methods: We conducted the survey of HTP use in the participants of the Tsuruoka Metabolomics Cohort Study, a prospective cohort including 11, 002 participants aged 40-74 in Japan. All data were obtained in the follow-up (2018-2019) and baseline (2012-2013) survey. Smoking habits were categorized to five groups according to follow-up survey; never smokers (NS), past smokers (PS), cigarette only smokers (CS), HTP only smokers (HS) and dual smokers (DS). Linear regression analysis was performed to examine the association between smoking habits and change of number of smoking tobacco products during follow-up. Results: Prevalence of HTP user was 12.4% in 40-59 years of age and 1.8% in 60-79 for male, and 1.7% in 40-59 and 0% in 60-79 for female. Dual smokers accounted for 34.9% of all HTP users. Change of smoking number during follow-up (5.7±0.8 years) was +3.11 (95%CI: 1.17, 5.07) in DS and -1.09 (-2.70, 0.53) in HS compared with CS, after adjusted for age, sex and smoking number at baseline. Conclusions: HTPs smoking including dual smoking was getting popular in Japan. Shift to HTPs was unlikely to affect the number of smoking tobacco, but dual smokers tended to smoke more than at baseline. Key messages: Dual smokers of cigarettes and HTPs tended to smoke more than before introducing and spreading HTPs.